PEMASANGAN JARINGAN INTERNET BERBASIS WIRELESS FIDELITY (WIFI) DI KAMPUNG WANGUN CIPURUT - Telly Rosdiyani (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
The Internet today makes a basic need in the fulfillment of the needs of people in the digital age, where during the COVID-19 pandemic demanded limited direct interaction to prevent the spread of viruses, the government digitized in supporting people to be able to work and learn. That certainly requires smooth internet network in each region. Similarly, in Kampung Wangun Cipurut is located in Batukuwung Village padarincang district of Serang Regency, one of the areas that is difficult to reach by other communities. Because, the terrain of the road to get to the location is still difficult to get through, so the internet network is very needed in the information of the development of the area. As for the problem how Cipurut Wangun Village requires the development of internet network, What is the purpose of Cipurut Wangun Village to build an Internet network, How to open a new business by utilizing Internet Network (Technology), How to benefit from the advancement of internet network technology that has been built one of the citizens there Author tried to create a network that could possibly be utilized for all residents of Kampung Wangun by utilizing WiFi network. Partner cooperation of a tower triangle at the central point of the server and planted several radios to channel to several points in Kampung Wangun Cipurut, The results obtained by the network become a great opportunity for the people in the village to open a home-based entrepreneurial industry facilitated by the village through BUMNDes.